Підготовка фахівців сфери туризму з огляду на потреби регіонального ринку - Щука Галина; Shchuka Halyna; Scsuka Halina; Гальків Любов; Halkiv Lyubov (РВВ ЦДПУ ім. В. Винниченка, 2020)
Резюме. В статті визначаються умови, які дозволять вирішити проблему якісного кадрового забезпечення регіональних туристичних ринків України. З цією метою на прикладі вирішення кадрових проблем туристичних комплексів Закарпаття з використанням методу експертного опитування встановлюються вимоги, які висувають працедавці до випускників туристичних спеціальностей; аналізується, які з цих вимог і наскільки повно задовольняються в процесі підготовки; виокремлюються ті очікування, які не задовольняються; пропонуються конкретні кроки щодо вдосконалення навчального процесу.

Abstract. This article is devoted to the actual problem of providing the regional tourism markets with highquality specialists. It is found that, despite the large number of higher education institutions that train specialists for the tourism industry and the constant updating of educational standards, tourism businesses and organizations in the country suffer from a lack of competent specialists, while graduates cannot find work in their profession. The research has been conducted in Transcarpathian region by the method of expert survey of owners and managers of successful tourism enterprises. The research technology is presented in details: a step-by-step definition of the nature of the requirements that employers impose the graduates of tourist specialties; analysis of educational standards and work programs of educational disciplines to meet these requirements in the preparation process; identification of reasons that do not allow to prepare the muchneeded specialist on the regional labour market in higher education institutions; concrete steps are suggested to improve the educational process. It is found that the learning outcomes laid down in the educational standards are determined by the manufacturer of educational services, they are more oriented to the needs of large tourism enterprises, and do not meet the needs of employers at least because most tourist enterprises and organizations in the country are small and medium in size. Training programs shall be focused on regional tourism markets, since the requirements for tourism professionals differ depending on the type of tourism activity, the size of the enterprise, the region of its operation. Owners of tourist complexes in Transcarpathia prefer to see at their enterprises multi-skilled managers (specialists), who are immediately ready to fulfill their functional responsibilities in their primary positions. For solving the problem of human resources in the tourist market of Transcarpathia it is recommended: to define and detail the expectations of the heads of regional tourism enterprises; to prepare curricula and work programs in accordance with these expectations, formulating learning outcomes in accordance with SMART technologies; to create the conditions for the implementation of these programs.
Training of tourism specialists catering to the needs of regional market
Keywords: професійна освіта в туризмі; компетентність; фахівець сфери туризму; менеджер широкого профілю